d° Ferromagnetism of Magnesium Oxide - Singh, J.P.; Chae, K.H. (MDPI AG, 2017)
Magnetism without d-orbital electrons seems to be unrealistic; however, recent observations of magnetism in non-magnetic oxides, such as ZnO, HfO2, and MgO, have opened new avenues in the field of magnetism. Magnetism exhibited by these oxides is known as d？ ferromagnetism, as these oxides either have completely filled or unfilled d-/f-orbitals. This magnetism is believed to occur due to polarization induced by p-orbitals. Magnetic polarization in these oxides arises due to vacancies, the excitation of trapped spin in the triplet state. The presence of vacancies at the surface and subsurface also affects the magnetic behavior of these oxides. In the present review, origins of magnetism in magnesium oxide are discussed to obtain understanding of d？ ferromagnetism. ？ 2017 by the authors. Licensee MDPI, Basel, Switzerland.